Health Expenditure Shocks and Household Poverty Amidst COVID-19 in Uganda: How Catastrophic? - Dablin Mpuuga; Sawuya Nakijoba; Bruno L. Yawe (Economies)
In this paper, we utilize the 2019/20 Uganda National Household Survey data to answer three related questions: (i) To what extent did out-of-pocket payments (OOPs) for health care services exceed the threshold for household financial catastrophe amidst COVID-19? (ii) What is the impoverishing effect of OOPs for health care services on household welfare? (iii) What are the socioeconomic and demographic determinants of OOPs for health care services in Uganda? Leveraging three health expenditure thresholds (10%, 25%, and 40%), we run a Tobit model for “left-censored” health expenditures and quantile regressions, and we find that among households which incur any form of health care expense, 37.7%, 33.6%, and 28.7% spend more than 10%, 25%, and 40% of their non-food expenditures on health care, respectively. Their average OOP budget share exceeds the respective thresholds by 82.9, 78.0, and 75.8 percentage points. While, on average, household expenditures on medicine increased amidst the COVID-19 pandemic, expenditures on consultations, transport, traditional doctors’ medicines, and other unbroken hospital charges were reduced during the same period. We find that the comparatively low incidence and intensity of catastrophic health expenditures (CHEs) in the pandemic period was not necessarily due to low household health spending, but due to foregone and substituted care. Precisely, considering the entire weighted sample, about 22% of Ugandans did not seek medical care during the pandemic due to a lack of funds, compared to 18.6% in the pre-pandemic period. More Ugandans substituted medical care from health facilities with herbs and home remedies. We further find that a 10% increase in OOPs reduces household food consumption expenditures by 2.6%. This modality of health care financing, where households incur CHEs, keeps people in chronic poverty.